Not by Gods but by People: The Story of Bella Hall Gauld - Vance, Catharine (Progress Books, 1968)
Her life spanned two centuries and led from pioneer social welfare work and church activity as a contemporary of J.S. Woodsworth to directorship of Canada's first University Settlement house in Montreal; and then forward to the larger horizons of the modern day labour and socialist movement. Bella Hall's epitomizes the unceasing struggle of ordinary men and women for a better life and is a tribute to the real makers of Canada. --Publisher's description
Keywords: Gauld, Bella Hall, 1878-1961